Ethnic Problem in Pakistan: A Case of Baluchistan (1999-2013) - Asia Saif Alvi; Farzana Zaheer Syed, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
Baluchistan's stability is highly reliant on the influence of various factors that have failed since its inception. Despite its enormous geostrategic importance and natural resource wealth, the province has experienced unrest and perturbations as a result of poor governance. Between 1999 and 2013, a qualitative research approach with an exploratory method was used to investigate the Balochistan mayhem in Pakistan. The primary and secondary sources used to learn about Balochistan's issues and problems. The current study sought to identify the major ethnic schisms in Balochistan from 1999 to 2013. How did insurgencies begin in Balochistan during the General Musharraf era? And what were the reasons for the ethnic mobilization of Baloch in the province? It is noted that the holistic approach of the Federal and Provincial governments can help Balochistan get out of its current bind. The political diffusion has created a nonconforming landscape. It provides a realistic transformation mechanism to address this simmering issue. According to the study, the lessons from the East Wing's political unrest in the 1970s should be learned and a wayout policy should be devised and implemented because people in Balochistan are patriotic.